علاقة أساليب التفكير بالقدرة على حل المشكلات لدى عينة من تلاميذ الثانية ثانوي - بن ناصر, فرحات (جامعة الوادي University of Eloued, 2017)
هدفت الدراسة إلى التعرًف على طبيعة العلاقة بين أساليب التفكير والقدرة على حل المشكلات لدى عينة من تلاميذ السنة الثانية الثانوي ببعض ثانويات دائرة مقرة ولاية المسيلة للموسم الدراسي2015/2016، التي بلغ عدد أفرادها (270) تلميذا وتلميذة مسحوبة بالطريقة العشوائية من ثانويات دوائر الولاية وأستخدم الباحث أداتين لجمع البيانات أحدهما لأساليب التفكيرتعريب وتقنين أبو هاشم (2007) والأخرى للقدرة على حل المشكلات تعريب وتقنين"حمدي نزيه(1998) ،"وقد توصلت الدراسة إلى وجود علاقة إرتباطية ذات دلالة إحصائية بين بعض أساليب التفكير والقدرة على حل المشكلات لدى عينة الدراسة كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية في أساليب التفكير وفي القدرة على حل المشكلات تعزى لمتغيري الجنس والتخصص. The study aimed to identify the relationship between thinking styles and the ability to solve problems within sample of secondary schools students in the district of Magra, city of M’sila for the academic year 2016/2015. The sample consisted of (270) male and female student who were chosen in a random sampling from secondary schools in the district of Magra. The researcher used two tools for data collection, one of them is thinking styles inventry (translated into Arabic and standardized by Abu Hashim and Kamel (2007), the other is the problemsolving scale (translated into Arabic and standardized by Hamdi Nazih (1998), the study found that there is a statistically significant correlation between some thinking styles and problem solving among the sample study. The results showed also that there are no statistically significant differences in thinking styles and the ability to solve problems related to specialization, or sex
دراسة ميدانية ببعض ثانويات دائرة مقرة المسيلة
مقال
Keywords: أساليب التفكير؛القدرة على حل المشكلات; Thinking Styles; Problem solving ability